Microlearning-Based Mobile Learning Module in Optimizing Learning Management System (LMS) - Lolang, Enos; Putra Pratama, Muh. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
In higher education institutions, one of the main challenges faced by students is how to understand complex lecture material, especially in computer application courses. This study aims to create a mobile learning module based on microlearning that is integrated with a Learning Management System (LMS) to improve the effectiveness of learning in computer application courses. This study is a development research. The subjects of this study were 40 students from the educational technology program, with a purposive sampling technique and the sample size determined using the Slovin method. The analysis results showed that the majority of students preferred mobile devices for learning and favored video-based media, followed by interactive simulations. The data also revealed that 95% of students had adequate internet access, while 5% faced challenges. The developed microlearning modules cover various computer application topics, such as Microsoft Word, Excel, and PowerPoint, presented through video-based content, interactive simulations, and practical exercises integrated into SPADA. The feasibility test of the modules by subject matter experts and media experts showed that the developed modules meet the criteria for high feasibility. The integration of microlearning modules into the LMS provides learning flexibility and supports a more inclusive, interactive, and effective learning process. This research makes a significant contribution to technology-based learning innovation in higher education, particularly in addressing learning challenges in the digital age.